Bibliometric analysis of neuroinflammation and Alzheimer’s disease - Sun, Wenxian; Gong, Jin; Li, Shaoqi; Wang, Pin; Han, Xiaodong; Xu, Chang; Luan, Heya; Li, Ruina; Wen, Boye; Wei, Cuibai (Frontiers in Aging Neuroscience, 2024)
Background Alzheimer’s disease (AD) is the predominant cause of dementia on a global scale, significantly impacting the health of the elderly population. The pathogenesis of AD is closely linked to neuroinflammation. The present study employs a bibliometric analysis to examine research pertaining to neuroinflammation and AD within the last decade, with the objective of providing a comprehensive overview of the current research profile, hotspots and trends. Methods This research conducted a comprehensive review of publications within the Science Citation Index Expanded of the Web of Science Core Collection Database spanning the years 2014 to 2024. Bibliometric analyses were performed using VOSviewer (version 1.6.19) and CiteSpace (version 6.3.R1) software to visualize data on countries, institutions, authors, journals, keywords, and references. Results A total of 3,833 publications on neuroinflammation and AD were included from January 2014 to January 2024. Publications were mainly from the United States and China. Zetterberg, Henrik emerged as the author with the highest publication output, while Edison, Paul was identified as the most cited author. The most productive journal was Journal of Alzheimers Disease, and the most co-cited was Journal of Neuroinflammation. Research hotspot focused on microglia, mouse models, oxidative stress, and amyloid-beta through keyword analysis. Additionally, keywords such as blood–brain barrier and tau protein exhibited prolonged citation bursts from 2022 to 2024. Conclusion This study provides a comprehensive review of the last 10 years of research on neuroinflammation and AD, including the number and impact of research findings, research hotspots, and future trends. The quantity of publications in this field is increasing, mainly in the United States and China, and there is a need to further strengthen close cooperation with different countries and institutions worldwide. Presently, research hotspots are primarily concentrated on microglia, with a focus on inhibiting their pro-inflammatory responses and promoting their anti-inflammatory functions as a potential direction for future investigations.